Construct validity of the Heart Failure Screening Tool (Heart‐FaST) to identify heart failure patients at risk of poor self‐care: Rasch analysis. (25th March 2018) - Reynolds, Nicholas A.; Ski, Chantal F.; McEvedy, Samantha M.; Thompson, David R.; Cameron, Jan
Abstract: Aim: The aim of this study was to psychometrically evaluate the Heart Failure Screening Tool (Heart‐FaST) via: (1) examination of internal construct validity; (2) testing of scale function in accordance with design; and (3) recommendation for change/s, if items are not well adjusted, to improve psychometric credential. Background: Self‐care is vital to the management of heart failure. The Heart‐FaST may provide a prospective assessment of risk, regarding the likelihood that patients with heart failure will engage in self‐care. Design: Psychometric validation of the Heart‐FaST using Rasch analysis. Method: The Heart‐FaST was administered to 135 patients (median age = 68, IQR = 59–78 years; 105 males) enrolled in a multidisciplinary heart failure management program. The Heart‐FaST is a nurse‐administered tool for screening patients with HF at risk of poor self‐care. A Rasch analysis of responses was conducted which tested data against Rasch model expectations, including whether items serve as unbiased, non‐redundant indicators of risk and measure a single construct and that rating scales operate as intended. Results: The results showed that data met Rasch model expectations after rescoring or deleting items due to poor discrimination, disordered thresholds, differential item functioning, or response dependence. There was no evidence of multidimensionality which supports the use of total scores from Heart‐FaST as indicators of risk. Conclusion: Aggregate scores from this modified screening tool rank heart failure patients according to their "risk of poor self‐care" demonstrating that the Heart‐FaST items constitute a meaningful scale to identify heart failure patients at risk of poor engagement in heart failure self‐care.